A phosphine-free Mn(i)-NNS catalyst for asymmetric transfer hydrogenation of acetophenone: a theoretical prediction. Issue 41 (30th September 2021) - Zhao, Yaqi; Zhang, Lin; Pu, Min; Lei, Ming
Abstract : A well-defined phosphine-free Mn(i )-NNS complex was proposed to be able to catalyze asymmetric transfer hydrogenation (ATH) of ketone. The reaction mechanism of ATH and the origin of stereoselectivity were investigated using DFT method. Abstract : The density functional theory (DFT) method was employed to investigate the reaction mechanism of the hydrogen activation and asymmetric transfer hydrogenation (ATH) of acetophenone catalyzed by a well-defined phosphine-free Mn(i )-NNS complex. The calculation results indicate that the Mn-NNS complex has potential high catalytic hydrogenation activity. Meanwhile, the hydrogen transfer step of this reaction is proposed to be a concerted but asynchronous process, and the hydride transfer precedes proton transfer. This work also pointed out that the stereoselectivity of ATH catalyzed by the Mn(i )-NNS complex mainly originates from the noncovalent interaction between the substrate and the catalyst. Additionally, the catalytic activities of Mn-NNS complexes with different X ligands (X = CO, Cl, H, OMe, NCMe, CCMe, and CHCHMe) were compared, and the calculated total reaction energy barriers were all viable, which indicates that these Mn-NNS complexes show higher CO bond hydrogenation activity under mild conditions. This theoretical study predicts that the reactions catalyzed by complexes with H and NCMe ligands exhibit high stereoselectivity with enantiomeric excess (ee) values of 97% and 93%, respectively.